Optimalisasi Literasi Membaca Soal HOTS Taksonomi Bloom Pada Teks Non Sastra Siswa SMP - Ida Tri Wahyuni; Roekhan Roekhan; Dwi Sulistyorini (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Lack of reading corner facilities, teachers often give questions with the ability to understand and remember, making the literacy ability of reading non-literary texts still low at the level of junior high school grade VIII. The purpose of analyzing and describing students' abilities in working on reading literacy at the level of analyzing, evaluating, and creating. The method used in this study is quantitative with a descriptive approach. The sample in the study amounted to 78. Data collection in this study was in the form of tests, the data in this study were the results of literacy scores reading non-literary texts, and the analysis technique in this study used IBM SPSS statistics 26 starting from the mean, mode, median, highest and lowest values. The results of the study obtained a score of analyzing 76.99 with a high category, a score of evaluating 80.71 with a high category, and creating with a score of 46.79 with a low category. From the results of the study, it is necessary to have reading literacy exercises with the levels of analyzing, evaluating, and creating (C6). Improving students in analyzing abilities is given exercises related to structure and spelling marks. Then at the evaluating level, namely providing practice questions related to assessing correct work, defending an argument, criticizing texts that are right or wrong. Then, at the creation level, increase practice in creating texts, creating creative ideas, and creating titles for non-literary texts.